Phenomenological approach to interpret the effect of liquid flow modulation in trickle bed reactors at the particle scale - Ayude, María Alejandra (2005)
This work analyzes the influence of liquid flow modulation on the behavior of a reaction occurring in a spherical porous particle within a trickle bed reactor. A single first-order reaction between a gaseous reactant and a non-volatile liquid reactant is considered. Non-steady-state mass balances for gas and liquid reactants are formulated and solved under isothermal conditions in order to focus the analysis on the mass transport effects. Dynamic reactant profiles inside the catalytic particle are obtained for different cycling and system conditions. The enhancement factor (ε) due to periodic operation is defined to evaluate the impact of induced liquid flow modulation on reaction rate. Influence of cycling and system parameters on the enhancement factor is also reported for a wide range of conditions. Experimental trends observed by several authors can be explained with this approach.